SocArXiv: open archive of the social sciences (Center for Open Science, 2016)
SocArXiv, open archive of the social sciences, provides a free, non-profit, open access platform for social scientists to upload working papers, preprints, and published papers, with the option to link data and code. SocArXiv is dedicated to opening up social science, to reach more people more effectively, to improve research, and build the future of scholarly communication
Gesehen am 21.04.2020
Keywords: Website; Datenbank